FACTORS RELATED TO MIDWIVES’ COMPLIANCE WITH THE USE OF PPE LEVEL 2 DURING DELIVERY ASSISTANCE PROCESS IN THE COVID-19 PANDEMIC SITUATION - Lilin Turlina (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: The purpose of this study was to analyze factors related to compliance with the use of PPE Level 2 in midwives during delivery assistance process in the COVID-19 pandemic situation.Methods: This study used a descriptive analytic study with a cross sectional approach. A total of 45 midwives who worked in hospitals belonging to the Muhammadiyah association in East Java were participated in this study. The samples were obtained by simple random sampling. The data were collected from June to December 2021. The data were processed by using factor analysis which aimed to filter out which variables were the most superior or the most dominant from several variables selected by the researchers. The interpretation of factor analysis was based on 1) KMO value > 0.05 and Bartlett’s value <0.05, 2) Anti Image Matrices value > 0.50, 3) Communalities with Extraction value > 0.50, 4) Total Variance Explained, 5) Scree Plot with Eigenvalue > 1, and 6) Component MatrixResults: The results indicated that most (60%) of the respondents complied with the use of PPE while assisting childbirth during the COVID-19 pandemic. Two factors affected the compliance of midwives in using PPE Level 2 were 1) Factor 1 (experience) consisted of age, length of working, and attitude, 2) Factor 2 (knowledge) consisted of education and knowledgeConclusion: It is expected that in providing delivery assistance, midwives always use personal protective equipment as a preventive effort.